Structural characterization and forest potential for community management of Purus National Forest, Western Amazonia - Brandão, Pedro Christo (2020)
Purus National Forest (PNF), located in the municipality of Pauiní, Amazonas state, Brazil, has a high conservation status and a population of about one thousand inhabitants. However, the scarcity of environmental studies in a suitable scale for the PNF management planning demands studies that quantify and qualify the stock of resources, that identify the community demand and set sustainable forest production techniques. Thus, the objective of the present work was to analyze the floristic composition, forest structure and the forest management potential of part of a "terra firme" dense ombrophylous forest located in the Forest Management Unit (UMF-1) of Céu do Mapiá village, the largest populational nucleus of PNF. To do so, a forest inventory was made, sampling in a block of 12 parcels of 50x50m, and all trees with DBH ≥ 10 cm were measured. The floristic composition was carried out and the Shannon-Wiener diversity index and Pielou equability index were used to assess the biodiversity and the uniformity of the community. The structural forest analysis was based on the absolute and relative values of density, dominance, frequency, importance value and diameter distribution of the basal areas and volumetric estimates of the population. A total of 1,764 individuals, pertaining to 35 botanic families, 91 genera and 163 possible specimens were registered, emphasizing that less than 40% (65) were identified at the species level. The UMF-1 is characterized by the high floristic diversity (H'= 4.10), few dominant species (J = 0.81) and many species with low abundance. Out of the commercial species used by the community, three are among the ten species with the greatest importance value, a total of 26 possible commercial species of sustainable exploitation.